(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
The article provides brief information about the antioxidant activity of some natural plants used in folk medicine and their importance in medicine, especially in the prevention of vitiligo. The relevance of the problem of vitiligo is due to the widespread prevalence of this disease among the population, its significant impact on the psychosocial state of patients, and the lack of reliable methods of therapy. Today, the prevalence of vitiligo is 0.5-2% of the population and remains a serious problem in dermatology, since there is no specific treatment for this disease. In folk medicine, preparations of St. John's wort and garlic, prepared on their basis, are used for the prevention and treatment of various skin diseases - vitiligo, neurological disorders, ringworm, bedsores.